Unemployment insurance in the presence of an informal sector (2013)
We study the effect of UI benefits in a typical developing country where the informal sector is sizeable and persistent. In a partial equilibrium environment we characterize the stationary equilibrium of an economy where policyholders may be employed in the formal sector, short-run unemployed receiving UI benefits and long-run unemployed without UI benefits. We perform comparative static exercises to understand how UI benefits affect unemployed workers' effort to secure a formal job, their labor supply in the informal sector and leisure time. Our model reveals that an increase in UI benefits generates two opposing effects for the short-run unemployed. First, since search efforts cannot be monitored it generates moral hazard behaviours that lower effort. Second, it generates an income effect as it reduces the marginal cost of searching for a formal job and increases effort. The overall effect is ambiguous and depends on the relative strength of these two effects. Additionally, we show that an increase in UI benefits increases the efforts of long-run unemployed workers. Using data from Brazil to calibrate the parameters of the model we provide a simple simulation exercise which suggests that the income effect pointed out is not necessarily of second-order importance in comparison with moral hazard strength: An increase in UI benefits may increase unemployed workers efforts to secure a job in the formal sector, instead of increasing informal-sector work. This result softens the widespread opinion that the presence of dual labor markets is an obstacle to providing UI in developing countries.